Output factors of ionization chambers and solid state detectors for mobile intraoperative radiotherapy (IORT) accelerator electron beams - Güngör, Görkem (J Appl Clin Med Phys, 2019)
PURPOSE: The electron energy characteristics of mobile intraoperative radiotherapy (IORT) accelerator LIAC (®) differ from commonly used linear accelerators, thus some of the frequently used detectors can give less accurate results. The aim of this study is to evaluate the output factors (OFs) of several ionization chambers (IC) and solid state detectors (SS) for electron beam energies generated by LIAC (®) and compare with the output factor of Monte Carlo model (MC) in order to determine the adequate detectors for LIAC (®). METHODS: The OFs were measured for 6, 8, 10, and 12 MeV electron energies with PTW 23343 Markus, PTW 34045 Advanced Markus, PTW 34001 Roos, IBA PPC05, IBA PPC40, IBA NACP‐02, PTW 31010 Semiflex, PTW 31021 Semiflex 3D, PTW 31014 Pinpoint, PTW 60017 Diode E, PTW 60018 Diode SRS, SNC Diode EDGE, and PTW 60019 micro Diamond detectors. Ion recombination factors (k (sat)) of IC were measured for all applicator sizes and OFs were corrected according to k (sat). The measured OFs were compared with Monte Carlo output factors (OF(MC)). RESULTS: The measured OFs of IBA PPC05, PTW Advanced Markus, PTW Pinpoint, PTW microDiamond, and PTW Diode E detectors are in good agreement with OF(MC). The maximum deviations of IBA PPC05 OFs to OF(MC) are −1.6%, +1.5%, +1.5%, and +2.0%; for PTW Advanced Markus +1.0%, +1.5%, +2.0%, and +2.0%; for PTW Pinpoint +2.0%, +1.6%, +4.0%, and +2.0%; for PTW microDiamond −1.6%, +2%, +1.1%, and +1.0%; and for PTW Diode E −+1.7%, +1.7%, +1.3%, and +2.5% for 6, 8, 10, and 12 MeV, respectively. PTW Roos, PTW Markus, IBA PPC40, PTW Semiflex, PTW Semiflex 3D, SNC Diode Edge measured OFs with a maximum deviation of +5.6%, +4.5%, +5.6%, +8.1%, +4.8%, and +9.6% with respect to OF(MC), while PTW Diode SRS and IBA NACP‐02 were the least accurate (with highest deviations −37.1% and −18.0%, respectively). CONCLUSION: The OFs results of solid state detectors PTW microDiamond and PTW Diode E as well as the ICs with small electrode spacing distance such as IBA PPC05, PTW Advanced Markus and PTW Pinpoint are in excellent agreement with OF(MC). The measurements of the other detectors evaluated in this study are less accurate, thus they should be used with caution. Particularly, PTW Diode SRS and IBA NACP‐02 are not suitable and their use should be avoided in relative dosimetry measurements under high dose per pulsed (DPP) electron beams.